The Effect of Arabica Coffee Extract (Coffea arabica L.) on the Expression of Inflammatory Biomarkers and Histopathological Features of the Liver-Pancreas in Alloxan-Induced Diabetic Mice - Suyarta Efrida Pakpahan; Putri Miftahur Rizki; Putri Najwa Az-Zahra; Rendi Ramdhani (Postgraduate, University of Mataram, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia, oxidative stress, inflammation, and organ damage, particularly in the liver and pancreas. This study aimed to evaluate the antidiabetic and hepatoprotective effects of Arabica coffee extract (Coffea arabica L.) in alloxan-induced diabetic mice. Thirty male mice were divided into five groups consisting of a negative control, a positive control treated with glibenclamide, and three treatment groups receiving Arabica coffee extract at concentrations of 50%, 75%, and 100% for 21 days. Chlorogenic acid content was analyzed using High-Performance Liquid Chromatography (HPLC), while blood glucose levels and liver histopathology were assessed after treatment. The results showed that chlorogenic acid content reached 20.8% in the tubruk extract and 16.9% in the macerated extract. Administration of Arabica coffee extract significantly reduced blood glucose levels, with the highest reduction observed in the 100% extract group (65% on day 14 and 62% on day 21). Histopathological examination revealed improvement in liver tissue architecture, characterized by reduced parenchymatous degeneration, hydropic degeneration, and necrosis compared with the negative control group. These findings suggest that Arabica coffee extract possesses antihyperglycemic and hepatoprotective activities and may serve as a promising natural therapeutic agent for diabetes mellitus management